Parametric Optimization under Cryogenic Machining of Medium Carbon Low Alloy Steel EN-19 Using the Integrated Taguchi-Present Worth Method - Sunday Ayoola Oke (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2021)
Medium carbon low alloy steel En-19 is a commercially thriving work material with 0.30 to 0.50% as carbon content and 0.60 to 1.65% as manganese content. The wide range of uses of medium carbon steel is for shafts, crankshafts, forgings, axles, couplings and gears. Given the broad industrial usage, the optimization of this work material is currently indispensable since it is a pointer to the economic management of drilling resources and a justifiable metric for performance assessment and evaluation. However, the present optimization models during machining have inaccurate predictions as they exclude the economic aspect of the material. In this article, a new combined Taguchi (T) method-present worth (PW) method is presented to account for the present worth and the inflation rate of steel material within the optimization context using literature data. The amalgamation of the two-component methods of Taguchi and present work is done at the signal-to-noise calculation. Then the response table, optimal parametric setting, the performance flow diagram and the present worth values are finally established. For the results, the optimal parametric setting was ascertained as SP3FR2DOC1, obtained at 37.48 (level 3), 35.92 (level 2) and 36.31 (level 1) for speed, feed rate and depth of cut, respectively, interpreted as 900rpm (speed), 0.1mm/min (feed rate) and 0.5mm (depth of cut). The T-PW method yields PWSP (62.85) as 1st, PWFR (-64.64) as 2nd and PWDOC (-65.13) as the 3rd position. It was found that the speed parameter is the best based on the optimization cum economic aspect assessment. The T-PW method predicts the optimization behaviour while analysing the economic aspect of the steel material and would help plan the purpose. The findings in this study would assist to clarify the approach to analyzing the economic characteristics of the machining process.